A Simulation-Based Approach for the Automated Design of Fatigue Resistant Continuous Fibre-Reinforced Components - Gadinger, Marc; Bode, Christoph; Deutschmann, Torben; Krause, Dieter; Wartzack, Sandro (Proceedings of the 35th Symposium Design for X (DFX2024), 2024)
Fibre-reinforced plastics are increasingly being used in important structural components. Here they are often subjected to cyclic loading, which leads to a deterioration in material properties. However current design methods hardly take this fatigue behavior into account. Instead, they rely on conservative safety factors, resulting in over-dimensioned components. In order to realise the full lightweight potential, we propose an innovative method that enables a targeted design for a defined service life. It integrates knowledge from experimental fatigue testing and uses modified mathematical failure criteria to predict the degree of fatigue throughout the part. This allows us to adaptively reinforce fatigue critical areas, resulting in lightweight and fatigue resistant structure
Keywords: fatigue behavior; fibre-reinforced plastics; lightweight design; optimization

Consideration of operational wear in tolerance analysis for process-oriented tolerancing - Bode, Christoph; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2022)
Besides manufacturing-induced part deviations, operational wear in persistent moving assemblies leads to time-dependent deviations of part geometries and the functionality of the mechanism. This article presents an approach based on the Archard wear model to predict the lifetime functionality of an assembly by carrying out a tolerance analysis, considering both, time-dependent variations in wear activity due to volume loss and the impact of process-induced geometrical variation on the wear. The novelty of this approach lies in the consideration of time-varying operational wear effects in tolerance analysis and non-conformance rate estimation. To prove its applicability, the approach is applied to a one-way-clutch.<br
CRIS-Team Scopus Importer:2024-12-16
Keywords: Tolerance analysis; Operational wear; Non-conformance rates

Entwicklung eines Vorgehens zur automatisierten Auslegung zyklisch belasteter, endlosfaserverstärkter Bauteile - Gadinger, Marc; Bode, Christoph; Wartzack, Sandro (Proceedings from the NAFEMS DACH Conference 2024, 2024)
Bauteile aus Faserverbundwerkstoffen werden zunehmend als wichtige Strukturbauteile im Serieneinsatz verwendet. Dort sind sie häufig zyklischen Belastungen ausgesetzt, die mit steigender Zyklenzahl durch Mikrorissbildung und -ausbreitung zu einer Verschlechterung bzw. Degradation der Werkstoffeigenschaften führen. Bisherige Auslegungsansätze und Optimierungsroutinen berücksichtigen die Betriebsfestigkeit jedoch kaum. Vielmehr erfolgt meist eine Überdimensionierung nach empirischen Kriterien. Um das volle Leichtbaupotenzial eines Bauteils auszuschöpfen, ist jedoch eine gezielte Auslegung auf eine definierte Lebensdauer zielführend. Um diese Lücke zur gezielten Betriebsfestigkeitsauslegung von Faserverbundbauteilen zu schließen, wird am KTmfk eine neue Auslegungsmethode zur Berücksichtigung des Ermüdungsverhaltens von Faser-Kunststoff-Verbunden entwickelt. Ziel ist dabei die lokale Verstärkung eines Basislaminats, um sicherzustellen, dass der Faser-Kunststoff-Verbund eine geforderte, minimale Schwingspielzahl erreicht. Dazu werden die im Bauteil wirkenden Spannungen und Dehnungen mittels einer Finiten-Elemente-Analyse ermittelt und örtlich aufgelöst pro Schicht und Element betrachtet. Mit Hilfe eines mathematischen Versagensmodells wird so für jedes Element die maximale bis zum Versagen ertragbare Schwingspielzahl berechnet. Die dafür notwendigen Kenntnisse über das anisotrope Festigkeitsverhalten liefern zyklische Versuche an unidirektionalen Probekörpern. Der erste Schritt zur Verbesserung des Langzeitverhaltens besteht darin, Patches an den in der Simulation identifizierten kritischen Bereichen anzubringen. Parallel dazu werden die Faserorientierungen der Lagen optimiert, indem sie an die Hauptrichtungen der größten Spannungen angepasst werden. Weitere Simulationen werden durchgeführt, um die Positionen und die Anzahl der Patch-Lagen, die Dicke der einzelnen Lagen und die Schichtreihenfolge zu optimieren. Das abschließende Post-Processing stellt sicher, dass am Ende der Optimierung ein fertigungsgerechtes Design vorliegt. Dazu werden ähnliche Patches mittels Clustering zusammengefasst. Die Neuheit und Einzigartigkeit dieses Ansatzes liegt in der Kombination der Laminatoptimierung dynamisch beanspruchter Strukturen mit der Flexibilität des Fiber Patch Placement. Damit ermöglicht die Methode eine flexible und gezielte Verbesserung des Betriebsfestigkeitsverhaltens unter Berücksichtigung des Leichtbaugedankens.<br
Keywords: Leichtbau; Betriebsfestigkeit; Laminatoptimierung; Faser-Kunststoff-Verbund

Holistisches Toleranzmanagement am Lehrstuhl für Konstruktionstechnik - Wartzack, Sandro; Götz, Stefan; Bode, Christoph; Franz, Michael; Freitag, Stephan; Horber, Dennis; Kramer, Vincent; Roth, Martin; Schächtl, Paul (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Implementation And Interpretation Of A Scrap And Failure Oriented Multi-Objective Optimization Considering Operational Wear - Bode, Christoph; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
The tolerancing of products for manufacturing is usually performed at the end of the design process and the responsibility of the designer. Although components are commonly tolerated to ensure functionality, time-based influences, like wear, that occur during operation, are often neglected. This could result in small amounts of scrap after production, but high quantities of failure during operation. To overcome this issue, this paper presents an approach to perform a multi-objective optimization considering tolerances based on a wear simulation. Thereby, mean shifts serve as optimization variables, while the aim of the optimization is to generate an optimal ratio of scrap to failure. In addition, the optimization results are interpreted and further options for the designer are presented. Moreover, the approach is exemplary applied to a use cas
Keywords: Tolerance representation and management; Optimisation; Simulation; Scrap and failure; Operational wear

Influence of metal gear tooth geometry on load and wear within metal-polymer gear pairs - Rohrmoser, Andreas; Bode, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Wartzack, Sandro; Merklein, Marion (Applied Sciences, 2022)
Gear pairs made of the material pairing metal-polymer provide advantages, such as a reduced weight, beneficial damping properties and the possibility to be operated in dry running conditions. However, the service life of the pairing is limited due to wear. The properties of the metallic gearing have a significant influence on the wear behavior of the material pairing. From previous investigations, the influence of the surface topography and the flank hardness of the metal pinion is known. With regard to resource saving and efficient manufacturing of the metal pinion, cold forging offers benefits. Through cold forging, metallic gears for the material pairing can be produced ready-to-use in a process suitable for serial production. In order to enable manufacturing by extrusion, the application of gear radii is necessary. The gear radii significantly affect the extrusion process and the achievable gear properties. However, the influence of gear radii on wear within the metal-polymer material pairing has not yet been investigated. Within this contribution, the influence of the gear radii on the contact behavior as well as the resulting local load and wear of the tooth flank is determined. For this purpose, wear tests with aluminum (AlMgSi1) and steel (16MnCr5) gears with different gear radii within the pairing with polyamide (PA66) gears were performed. It has been shown that the local wear of the tooth flank can be attributed to the local load and that adjusted gear radii lead to a varying load and wear of the metal and polymer gears. Based on the findings, functional relationships regarding the choice of gear radii and the wear behavior are derived which can be applied in the design of cold forged gears.
Created from Fastlane, Scopus look-up
Keywords: Gear; Metal; Polymer; Tooth contact; Tooth geometry; Wear

On the transferability of nominal surrogate models to uncertainty consideration of clinch joint characteristics - Bode, Christoph; Götz, Stefan; Wartzack, Sandro (Procedia CIRP, 2024)
The mechanical joining process clinching is becoming increasingly important, especially for multi-material car body elements enabling lightweight design. However, the design of these joining points is usually based on expert knowledge and time-consuming experiments. For this reason, simulations are used in combination with surrogate models to predict the characteristics of clinch points for specific process parameters. Thereby, the process parameters are assumed to be ideal, so that inherent uncertainties are currently neglected. In order to overcome this deficiency and ensure a realistic prediction of clinch point characteristics, a consideration of variations is inevitable. Therefore, this paper analyses the transferability or significance of the nominally predicted values of existing surrogate models for clinch joints, taking into account process parameters with unavoidable variations. This shows, that the nominal parameter configuration affects the scattering of joint characteristics when considering variations. Moreover, implications for the necessary additional sampling in order to increase the significance of existing (nominal) surrogate model predictions are given, while considering the additional computational effort involved.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Clinching; Sampling; Simulation; Surrogate modeling; Uncertainty

Process-Oriented Tolerance and Variation Management: Review and Classification - Litzenburger, Philipp; Götz, Stefan; Margies, Lennard; Bode, Christoph; Müller, Rainer; Wartzack, Sandro (Applied Sciences, 2024)
In the context of tolerance management, the consideration of manufacturing and assembly processes is becoming increasingly important. The main drivers for this are, above all, short development times and high-quality requirements, leading to tight tolerances. To overcome the resulting challenges, many publications address the process-oriented tolerance management. However, since multiple terms and definitions for describing activities that link tolerance management with the production process exist, it is hard to obtain a comprehensive overview on the topic. Therefore, this paper presents a review of existing approaches. The aim is to identify similarities and differences of existing approaches and present them with the help of a classification. For this purpose, among others, work from the areas of process-oriented tolerance management, stream of variation, state space modeling, and variation propagation in multistation manufacturing and assembly systems is considered. Based on the definition of the summarizing term “process-oriented tolerance and variation management”, a classification of this thematic area will be introduced.<br
Keywords: process-oriented tolerancing; stream of variation; state space modeling; process-oriented tolerance and variation management

Process-Oriented Tolerancing: Consideration of Manufacturing and Operation for Product Assurance Using Virtual Methods - Bode, Christoph; Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Research in Tolerancing, 2024)
A product generally proceeds through development, production and assembly before it goes into operation. In particular, iterations often occur between development and production, although information are usually only passed on systematically in one direction. Errors during development and especially during tolerancing, scheduled at the end of the development phase, are therefore usually not discovered until production, assembly, or operation. The risk of such errors is particularly high in tolerancing for two reasons. First, tolerancing is usually based on expert knowledge or standards, which covers a large proportion of standard cases, but not every case. Second, conventional tolerancing usually focuses on ensuring functionality at the end of production. The manufacturability and the influence of operation in terms of wear are usually not considered. The aim of process-oriented tolerancing is to provide information from production and operation early in the development phase and especially in tolerancing. This enables the tolerance engineer to ensure manufacturability and functionality before and during operation. This chapter provides an overview of process-oriented tolerancing. Both state-of-the-art approaches and a novel holistic approach using virtual methods are presented. The novel approach aims to include all areas involved in tolerancing and to reduce iterations and the time required for testin

Teilprojekt 1: Virtuelle und experimentelle Toleranzuntersuchungen abweichungsbehafteter Baugruppen - Bode, Christoph; Schleich, Benjamin; Wartzack, Sandro (Abschlussbericht DFG-Forschungsgruppe FOR 2271, 2. Phase. Prozessorientiertes Toleranzmanagement mit virtuellen Absicherungsmethoden, 2023)

Tolerancing in product design – a holistic description scheme - Götz, Stefan; Roth, Martin; Schächtl, Paul; Kramer, Vincent; Bode, Christoph; Horber, Dennis; Franz, Michael; Freitag, Stephan; Miehling, Jörg; Wartzack, Sandro (Design Science, 2025)
Along with increasing product complexity and quality requirements, the consistent consideration of inevitable production-induced variations within the product development process becomes a decisive factor for the market success of products. Consequently, various tolerancing approaches have emerged over the last few decades. However, tolerancing is considered complex in education, research, and industry, as it is a highly interdisciplinary task that takes place at different levels of detail, ranging from Robust Design to tolerance specification to manufacturing process design. This contribution proposes a novel approach that allows a holistic and structured description of tolerancing and fosters a common understanding among all involved stakeholders from design, manufacturing, and inspection. This is achieved by categorizing it into several distinct elements: activities, methods, tools, models and data, information, and knowledge. This ensures clarity and supports the utilization of existing approaches. While this contribution focuses on tolerancing in product design, the linkage to subsequent product realization stages and further engineering domains is also addressed in the proposed description scheme. An exemplary classification of research papers and a description of a practical development process of a technical system with its different tolerancing activities illustrate the benefits of the proposed description schem
Keywords: Tolerancing; Dimensional Management; Variation Management; Robust Design; Product Design